Pengaruh Budaya Kaizen Terhadap Kinerja Karyawan Pada Pt Pegadaian (Persero) Area Palembang - Sibarani, Eka Ramadhanty; Asmanita, Asmanita (Syntax Literate, 2023)
Employee performance is a description of the company's performance. The factor to improve employee performance is how to create a strong work culture, namely the kaizen culture. Kaizen culture itself is a small improvement in a process that can continuously involve all aspects, namely top management, managers to employees. Kaizen culture proves its success in Japan, thus there will be an opportunity to bring success to companies in Indonesia in implementing it, this study entitled The Effect of Kaizen Culture on Employee Performance at PT Pegadaian Palembang Area. The purpose of this study was to determine the influence of kaizen culture on employee performance. The object of this research is PT Pegadaian Area Palembang with simple random sampling of 36 (thirty six) employees who become respondents. The data analysis technique used simple regression analysis to partially test the effect. The partial test shows that kaisen culture has an influence on employee performance. The results of the study stated that there was a significant influence between kaizen culture on employee performance at PT Pegadaian Area Palembang. Based on the indicators that have been tested, the previous results show that the kaizen culture and after using the kaizen culture have significant differences. There is meaning in using kaizen culture which greatly influences employee performance much better than before using kaizen culture.